Ethanolic extract of Casearia sylvestris Sw exhibitsin vitro antioxidant and antimicrobial activities andin vivo hypolipidemic effect in rats - J. ESPINOSA; L.F. MEDEIROS; A. SOUZA; A.R.C. GÜNTZEL; B. RÜCKER; E.A. CASALI; E.M. ETHUR; M.R. WINK; I.L.S. TORRES (Revista Brasileira de Plantas Medicinais, 2015)
ABSTRACT:The Casearia sylvestris Sw (Flacourtiaceae) is a shrub that occurs in forests of Southern Brazil; its leaves are widely used in folk medicine as a depurative, analgesic, anti-inflammatory and antiulcerogenic agent. The objective of this study was to perform the phytochemical description and to evaluate the pharmacological activities (antimicrobial, antifungal, antioxidant and toxicity) of the ethanolic extract (EE) of C. sylvestris Sw. In addition, we also evaluated the effect of the EE ofC. sylvestris Sw on the glucose levels and lipid profile in blood serum of rats submitted to a model of streptozotocin-induced diabetes. Material and Methods: In vitro assay: the detection of chemical groups was done through chemical reactions with the development of color or precipitate and by chromatographic profile; the antioxidant activity was measured by the method of reduction of DPPH free radical (2,2-diphenyl-1-picrylhydrazyl); the Minimum Inhibitory Concentration was evaluated by the broth microdilution method, and the Minimum Bactericide Concentration and the Minimum Fungicide Concentration were performed in Petri dishes; the cytotoxic activity was measured by the Artemia salina test. In vivo assay: diabetic and non-diabetic rats were treated with EE of C. sylvestris Sw (300 mg/kg) for 45 days, and the glycaemia and lipid profile were analyzed. Results: The EE showed a Lethal Dose50 of 724.76 μg.mL-1 and important antioxidant, fungicide and fungistatic activities. The EE showed better antimicrobial activity regarding the microorganismsStaphylococcus aureus, Escherichia coli andSalmonella setubal. Conclusion: The EE of C. sylvestris Sw produces a significant decrease in triglycerides, total cholesterol and VLDL levels without any significant alteration in the glycaemia. The EE of C. sylvestris Sw presents antioxidant and antimicrobial activities and it exhibits a potent hypolipidemic effect.